2008
DOI: 10.1159/000123706
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Locking Solution Spillage: Theory and Experimental Verification

Abstract: A theory was developed allowing the prediction of the spillage volume after injection of locking solution into a catheter. This theory was corroborated by in-vitro measurements using colorized fluid injected automatically by a micropump into a stirred container with clear fluid. The amount of spilled solution was measured with a fiberoptic spectrometer equipped with a dip probe. Straight cylindrical tubing was used as catheter. Results: The theory predicts the beginning of spillage when 50% of the catheter fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
0
27
1
Order By: Relevance
“…[35], [36] In clinical practice, lock solution is always partly spilled into the systemic circulation when instilled and often has to be injected completely if aspiration is not feasible. [17] The current standard to obviate precipitation reactions in agents used as anticoagulants for CVCs focuses solely on the pure lock solution. [37], [38] However, this approach might be inadequate if the fluid density of the analyzed lock solution is different from blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35], [36] In clinical practice, lock solution is always partly spilled into the systemic circulation when instilled and often has to be injected completely if aspiration is not feasible. [17] The current standard to obviate precipitation reactions in agents used as anticoagulants for CVCs focuses solely on the pure lock solution. [37], [38] However, this approach might be inadequate if the fluid density of the analyzed lock solution is different from blood.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, leakage of catheter lock solutions into the systemic circulation of approximately 20–25% at the time of instillation has been demonstrated repeatedly. [17][18] Several authors reported increased aPTT times or bleeding episodes if heparin was instilled to lock CVCs. [19][21] The spillage during instillation of the listed filling volume into the CVC is a physical consequence of parabolic rather than plug flow distribution within the catheter and thus cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly demonstrated in large numbers of papers over the last 10 years; nearly without exception; showing substantial reduction in catheter-related bloodstream infection. However, Polaschegg discoverered a problem and he showed with theory and experimental data that a considerable amount of the lock spills out in vivo [12]. Loss of lock solution has various consequences including overdosing heparin and consequent bleeding risks, drug interactions, loss of lock protection in the catheter and enablement of blood entering the catheter.…”
Section: A New Systemmentioning
confidence: 99%
“…However, several recent studies have shown a significant prolonged activated partial thromboplastin time (aPTT) during retention of high-concentration heparin solution [2,3,4,5]. This phenomenon, which might increase the risk of bleeding, is caused by heparin leakage from the catheter [6,7,8,9]. A previous study has shown that heparin lock was associated with bleeding complication during tunneled HD catheter placement [10].…”
Section: Introductionmentioning
confidence: 99%